Concurrent testing of breeding bulls for bovine herpesvirus 1 infection (BHV-1) in India - Chintu Ravishankar; Sukdeb Nandi; Vishal Chander; Tapas Kumar Mohapatra (Veterinaria Italiana, 2013)
In this study, sera from 65 breeding and 19 training bulls from Uttar Pradesh State in north India were tested for bovine herpesvirus 1 (BHV-1) antibodies by enzyme linked immunosorbent assay (ELISA) and virus neutralization test (VNT). The VNT test could detect 56 (86.15%) and 9 (47.37%) of the samples from breeding and training bulls as positive for BHV-1 antibodies whereas in ELISA 63 (96.92%) and 10 (52.63%) were found positive, respectively. Semen samples from the breeding bulls were simultaneously tested by the Taqman based real time PCR (qPCR). Of the 65 samples screened, only 40 (61.54%) were found to contain BHV-1 DNA indicating that all the seropositive bulls are not shedding the virus in semen. When the RT-PCR positive samples were subjected to virus isolation on Madin-Darby bovine kidney (MDBK) cells, no virus isolates could be obtained. The advantages of concomitant testing of serum and semen of breeding bulls and measures for control of BHV-1 infections in bull farms are discussed.